V For Vendetta Novel Grafis sebagai Ikon Revolusi - Nadia Aghnia Fadhillah (Jurnal Kajian Seni, 2016)
Wave of protests shook the world. Thousands facescovered by strange mask with cynicalsmile fl ooded cities around the world. They are V’s masks, the main character of ‘V forVendetta’, a graphic novel, which was inspired by Guy Fawkes, a revolutionist whoattempted to bomb British Parliament Building. Anonymous, a hactivist organization,take V’s character as its identity. In October 2011, the biggest protests in historydemand for politic and economy equality: Occupy Movement. Anonymous took big rolein the movement. Guy Fawkes’ mask became popular. In online and offl ine activism ofAnonymous. The mask expresses social critics, represents the unheard voices of thefear. V for Vendettastartsrevolutionaround the world, it inspires rebellion, shows thatthere is always a way to fi ght and hope for the freedom.